THE EFFECT OF DIFFERENT POSITION OF GRAPE CLUSTERS ON THE BEARING SHOOT ON PRODUCTION RESULTS OF CABERNET SAUVIGNON CLONES - Čoloveić, Ana M.; Žunić, Dragoljub M.; Ljubanović Ralević, Ivana I.; Kalanović Bulatović, Branka M.; Lukač Bulatović, Mirjana Ž. (Economics of Agriculture, 2014)
In this paper the differences were examined between clones of Cabernet sauvignon (clones ISV-F-V5, ISV-F-V6 and R5), i.e. the difference between uvological properties of grape clusters and grape berries, based on the different positions on the bearing shoot. Tests were conducted at the experimental fled of the Faculty of Agriculture "Radmilovac." Standard ampelographic methods were used in numerous analyses of grape yield, as well as uvological properties of clones. All data were statistically analyzed and processed by the method of two-factor analysis of variance with repeated measuring of one factor (height) and Tukey HSD test. Analysis of variance showed no significant differences between clones. The best results were achieved with grape clusters positioned in the base of bearing shoot. The first positioned grape clusters on the bearing shoot had the highest share in the total grape yield, the highest amount of sugar, and the highest positioned grape clusters had higher content of total acids. The differences determined between examined clones were in regard to productivity and quality of grapes which reflected also on production value.